Case Report: Fatal prosthetic valve endocarditis due to Staphylococcus lugdunensis—a wolf in coagulase-negative clothing - Patel, Raj; Patel, Ekta; Patel, Riddhi (Frontiers in Medicine, 2026)
Staphylococcus lugdunensis is a rare but highly virulent coagulase-negative Staphylococcus (CoNS) capable of causing aggressive native and prosthetic valve endocarditis. Unlike other CoNS, it resembles S. aureus in its ability to rapidly destroy cardiac structures and cause systemic complications. We present a woman in her 70s with a prosthetic mitral valve who initially presented with altered mental status and was diagnosed with S. lugdunensis prosthetic valve endocarditis. Despite targeted intravenous antibiotics, her condition deteriorated rapidly, and she unfortunately died within 5 days of admission. This case highlights the need to distinguish S. lugdunensis from other CoNS and to recognize its aggressive course and limited response to antibiotics alone.